Measurement of solar radiation properties and thermal energy of the atmosphere in Rzeszow - Piotr Strzelczyk; Mariusz Szewczyk; Rafał Gałek; Paweł Gil (Advances in Mechanical and Materials Engineering, 2018)
This article presents measurement of solar radiation properties and thermal energy of the atmosphere in Rzeszów (φ = 50°02’N, λ = 22°17’E). The measurements include direct, diffuse and global solar radiation as well as thermal radiation from the atmosphere. Weather station provides six of the most important weather parameters: air pressure, temperature, humidity, rainfall, speed and direction. Sky radiometer with dedicated sun tracker provides multiband measurement of direct and diffuse solar radiation. Measurement results from over 4 years have been collected so far and may be used to estimate energy yields from solar systems. The article presents selected results of solar radiation and weather parameters in 2017.